Pembuatan Alat Pemeras Madu Lanceng untuk Skala Usaha Kecil Menengah – Gubuk Lanceng : Indonesia - Riza, Rahmat; Putro, Tri Setiyo; Puspaputra, Paryana (UII, 2024)
Honey is a food product produced by bees. Honey is obtained by separating the liquid honey from the beehive. At the Gubuk Lanceng Magelang farm, honey is still squeezed manually, which is squeezed by hand, so the honey obtained is not optimal and the propolis produced is irregular. The purpose of this study was to design a honey squeezer that could squeeze the hornet's nest while printing propolis into pieces by using a screw mechanism for the pressing process. The honey squeezer is made based on several criteria such as corrosion resistance, easy operation, easy cleaning, capable of printing propolis, and affordable prices for UMKM. The design includes the design and manufacture of components which include the frame, filter tube, container, turning lever, and pressure plate. The capacity of this tool itself is 4 kg. In testing the tool using a honeycomb weighing 300 grams and testing for 3 trials, the test results show that the honey squeezer can work better than hand squeezing. The test results show the efficiency of the honey squeezer is 45% compared to the hand squeeze which is only 29.5%. The resulting form of propolis also has the same shape and size as each other.